Evaluation of a social marketing campaign for the early detection of oral potentially malignant disorders and oral cancer: Sri Lankan experience - Hemantha Amarasinghe; Saman Warnakulasuriya; Newell W. Johnson (Journal of Oral Biology and Craniofacial Research)
Introduction: The present study evaluated a national social marketing campaign (SMC) conducted in 2008, with the ultimate aim of improving control of oral cancer in Sri Lanka. The approach was based on our published Risk Factor Model (RFM). Methods: Social marketing tools were developed to educate the public on the major risk factors for oral cancer. A cross-sectional community-based cluster survey was carried out in 2013 by interviewing 491 citizens >25 years of age to assess any improvements to the level of disease awareness in the community. Changes in the number of case presentations were obtained from registrations at Government Hospital Dental Clinics (GHDC) from the year 2008–2015. Results: A random sample of 491 members of the public was interviewed in 2013. Most (93%) were aware of oral cancer; but only 45.4% of oral potentially malignant disorders (OPMD). Statistically significant improvements were observed on awareness of oral cancer and OPMD and of the risk factors for oral cancer. A marked increase in the detection of oral leukoplakia and of oral cancer occurred in the GHDC surveillance system in the years 2012 and 2013, at the time the SMC campaign was implemented. Conclusion: The improvement in public awareness of oral cancer and of its major risk factors, and the changed public behavior seen in the increased attendance at healthcare facilities for mouth examination, may be attributed, at least in part, to our SMC. Such Risk Factor-based approaches to social marketing are proposed for control of oral cancer.